Overview on the Response Surface Methodology (RSM) in Extraction Processes - Khairul Anwar, Mohamad Said; Mohamed Afizal, Mohamed Amin (JASPE, 2015)
Response Surface Methodology (RSM) is an optimization tool that can identify interrelationship between variables as being adopted by experiment/ research studies in food and herbal plants extraction niche area. This review discusses the optimization approach through utilization of research surface methodology either using central composite design or Box-Behnken method specifically in extraction processes. The use of analysis of variance (ANOVA) to evaluate the degree of accuracy held by the derived model is based on several responses. RSM helps to determine the best experimental design in order to identify the relationship between variables. This paper also discusses on the utilization of RSM to derive a model equation that later can be applied for response prediction and the determination of optimal conditions.